An Innovative Food Processing Technology: Microwave Electrodeless Ultraviolet, Luminescence Mechanism, Microbial Inactivation, and Food Application - Shuqi Chang; Zhaoyi Zhang; Qin Liu; Haixia Wu; Alideertu Dong (Foods)
Microwave electrodeless ultraviolet (MWUV) technology, as an emerging food processing technique, has garnered growing attention in the realm of food science in recent years. Based on different application requirements, MWUV equipment types are categorized as microwave oven reactor, continuous-flow UV-microwave reactor, coaxially driven MWUV reactor, and complete ultraviolet reactor. The luminescence properties of MWUV equipment depend on their filler gas; mercury is commonly used as a filler gas to produce a wavelength at 253.7 nm for food non-thermal sterilization. The microbial sterilization effect of MWUV is primarily attributed to the synergistic action of microwave and ultraviolet (UV): MWUV enhances reactive oxygen species (ROS) production, disrupts the cell membrane structures of bacteria, leads to bacterial endosome leakage, and induces nucleic acid damage. MWUV extends food shelf-life by eliminating microorganisms without significantly altering food quality compared with traditional thermal sterilization methods. Additionally, MWUV, combined with digestion reagents such as HNO3 and H2O2, can effectively enhance the digestion of food samples to detect essential and toxic elements. Studies on MWUV technology hold broad potential in the food industry, with promising implications for food safety and consumer demand for high-quality food. Future research may focus on optimizing the equipment parameters and integrating with other food processing technologies to facilitate further development and application of MWUV.